Upaya Berbagai Pihak dalam Mengatasi Gizi Buruk untuk Mewujudkan Generasi Emas pada Anak Usia Dini - Najhwa Jananti Alfi; Ismaniar Ismaniar; Lili Dasa Putri (Jurnal Pendidikan Dirgantara, 2025)
Malnutrition among early childhood remains a critical issue that hinders Indonesia’s efforts to realize its Golden Generation. This study aims to describe the current condition of child malnutrition, its impacts, contributing factors, and strategies for prevention involving families, communities, health workers, early childhood education institutions, and the government. This paper uses a literature review method by examining scientific sources related to nutrition, early childhood development, and governmental policies. The findings indicate that severe malnutrition significantly affects children’s physical, cognitive, socio-emotional development, and long-term health. Contributing factors include low nutritional literacy, inadequate parenting practices, poor sanitation, recurrent infections, economic limitations, and suboptimal implementation of nutrition programs. Effective prevention requires an integrated, multisectoral approach involving nutrition education, growth monitoring, improved access to nutritious food, and strengthened interventions during the First 1000 Days of Life. Sustainable collaboration across sectors is essential to reduce malnutrition rates and support the development of a healthy and competitive future generation.